Development and metrological characterization of a precision force transducer for static force measurement related applications. (June 2016) - Kumar, Harish; Sharma, Chitra; Arora, P.K.; Moona, Girija; Kumar, Anil
Highlights: Design and development of octagonal ring shaped force transducer. Developed force transducer calibrated according to standard procedures. Metrological performance reveals suitability of the force transducer. Comparison with other simple shaped force transducers discussed. Abstract: The present paper discusses design and development of a force transducer of octagonal ring shape, which is a modified version of ring shaped force transducer. Nominal capacity of the force transducer designed and developed is 25 kN. This force transducer has been investigated for its utilization as force transfer standard for static force measurement and related applications. This force transducer is studied using dial gauge and strain gauges for its metrological characterization according to the calibration procedure based on standard ISO 376:2011/IS 4169:1988 (reaffirmed 2003) and is found to have good metrological results as compared to the existing ring shaped force transducers.